Pengembangan Media Lift The Flap Book Materi Pembagian untuk Meningkatkan Minat dan Keaktifan Belajar Siswa Kelas 2 di SDN Sidodadi 1 Garum - Kholfatur Rofi'ah; Fathul Niam; Aang Yudho Prastowo (Patria Educational Journal (PEJ), 2022)
This study aims to: produce a valid and effective lift the flap book to increase students' interest in learning mathematics. Initial data was collected only through classroom teacher interviews due to the Covid-19 fpandemic. fThe fresults fof fthe fpreliminary fstudy fare fused fas fthe fbasis ffor fmedia fdevelopment. fFurthermore, fdata fwere fcollected fby fobservation, fquestionnaires fand fdocumentation. fData fanalysis fused fquestionnaires fand fexpert fjudgment fsheets. fThe fresults fshowed fthat: f1) fthe fmedia fhas fmet fthe fvalidity fcriteria fbased fon fthe fresults fof fmaterial fvalidation fwith fa fpercentage fscore fof f90% fwhich fis fincluded fin fthe f"Very fValid" fcategory fand fthe fresults fof fmedia fvalidation fwith fa fpercentage fscore fof f95% fwhich fare fincluded fin fthe f"Very fValid" fcategory, fwhich fshows fthe fteacher fand fstudent fresponses f(very fgood) f2) fthe fdeveloped fmedia fis fable fto fincrease fstudent finterest fand flearning factivity fbased fon fa fcomparison fof fthe fpercentage fof fquestionnaires fbefore fand fafter fusing fthe fmedia. fThe faverage fpercentage fof finterest fin flearning fwhich fwas foriginally f59,97% fto f83,31%. fWhile fthe faverage fpercentage fof flearning factivity fwhich fwas foriginally f52,64% fto f882,63%. fThrough fthe media developed, students are able to increase their interest and learning activity.